EXPERIENCE IN THE TREATMENT OF DIAPHRAGMATIC HERNIA - Евгений Валерьевич Топаков; Орлан Валерийович Ооржак; Алина Игоревна Загорская; Екатерина Андреевна Шухова; Сергей Юрьевич Шост; Алексей Алексеевич Марцияш; Вадим Гельевич Мозес; Александр Анатольевич Шапкин; Александр Алексеевич Сашко (Медицина в Кузбассе)
Hernias of the diaphragm (HAP) are a common pathology that negatively affects the quality of life of patients and in some cases requires high-quality surgical correction. This pathology has a progressive course, which leads to an increase in the severity of clinical manifestations with the age of the patient. At present, behavioral and conservative therapy is the first line of treatment for HAP, while surgical correction is performed only if they are ineffective. This tactic helps to reduce the likelihood of discrediting surgical treatment and increase its effectiveness. The article presents the experience of surgical treatment of HAP on the basis of a large multidisciplinary hospital.